f(0) = ( f(k) +f(-k) ) / 2
f(0) = (16 - 4) / 2
f(0) = 12 / 2
f(0) = 6 → ANSWER
*Remember that f(0) = m(0) + n = n
If we have f(x) = mx + n, then:
f(k)= mk + n and f(-k)= -mk + n
If we add them:
f(k) + f(-k)
= mk + n -mk + n
= 2n
= 2f(0)
So we conclude that:
f(0) = [f(k) + f(-k)] / 2
27x^3-108x^2y+144xy^2-64y^3
Answer:
(a) Because it is an exterior angle
(b) The measure of angle 2 is 72°
Step-by-step explanation:
Angle 2 is an exterior angle because it is adjacent to the interior angle 1, and an exterior angle is equal to the sum of the measures of the two nonadjacent interior angles:
<2=30°+42°
<2=72°
Answer:
hola, por que? si 8xup3 euqlieas tja gnaot nighar
Step-by-step explanation:
Answer:
-8
Step-by-step explanation: